Subjective wellbeing of preschool children - Silva, Bianca Núbia Souza; Martins, Bianca Gonzalez; Campos, Lucas Arrais; Marôco, João; Campos, Juliana Alvares Duarte Bonini (Frontiers in Public Health, 2023)
Objective: The aim of the present study was to evaluate the psychometric properties of the Autoquestionnaire Qualité de Vie Enfant Imagé (AUQEI) in pre-school children and estimate the influence of demographic characteristics on their subjective well-being. Methods: Construct validity was estimated using confirmatory analysis and the chi-square per degrees of freedom ratio (2/df), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA). Reliability was assessed by the ordinal alpha (α) and omega (ω) coefficients and the factorial invariance by the difference in CFI (ΔCFI). Mean scores for each AUQEI item and the general score were calculated. Results: A total of 443 Preschool children enrolled in public education institutions participated. The original 4-factor AUQEI model showed collinearity between factors and a high correlation between two items. A single factor model was tested, presenting adequate fit to the data (2/df = 4.47; CFI = 0.98; TLI = 0.98; RMSEA = 0.08; α=0.98; =0.93; UniCo>0.95, EVC>0.85 and MIREAL<0.30) and strict model invariance (ΔCFI<0.01). The AUQEI model proved to be valid in relation to the external variables. Most children (76.7%) had positive subjective well-being. Higher scores were observed for items concerning recreation, holidays, and birthdays, and lower scores for those referring to hospitalization, medication, medical consultation, and being away from the family. The relationship between the demographic characteristics of the child or his/her mother and subjective well-being was not significant (p>0.05). Conclusions: The assessment of subjective well-being with the single-factor AUQEI model provided valid, reliable, and invariant. Thus, being a relevant and interesting instrument to assess well-being in young children.